2007
DOI: 10.1038/sj.bjc.6603583
|View full text |Cite
|
Sign up to set email alerts
|

Differences in the histological findings, phenotypic marker expressions and genetic alterations between adenocarcinoma of the gastric cardia and distal stomach

Abstract: Adenocarcinoma of the gastric cardia (C-Ca) is possibly a specific subtype of gastric carcinoma. The purpose of this study was to clarify the differences in the clinicopathological characteristics between C-Ca and adenocarcinoma of the distal stomach (D-Ca), and also the differences in the expressions of gastric and intestinal phenotypic markers and genetic alterations between the two. The clinicopathological findings in 72 cases with C-Ca were examined and compared with those in 170 cases with D-Ca. The pheno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
22
0
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 45 publications
1
22
0
2
Order By: Relevance
“…For example, CAC are strongly correlated with chronic gastroesophageal reflux (Wijnhoven et al, 1999) and with cigarette smoking (Gammon et al, 1997), and have a higher rate of lymph node metastasis and unfavorable prognosis (El-Rifai et al, 2001;Tajima et al, 2007), while Hp infection has been proven to be more relevant to GAC development (Xue et al, 2011). In the subgroup analyses by type of gastric cancer, we found significantly increased risk with all genetic models in GAC subgroup; however, nearly no remarkable changes in risk estimates was observed in CAC and GSCC subgroups for the NQO1 gene C609T polymorphisms.…”
Section: Discussionmentioning
confidence: 99%
“…For example, CAC are strongly correlated with chronic gastroesophageal reflux (Wijnhoven et al, 1999) and with cigarette smoking (Gammon et al, 1997), and have a higher rate of lymph node metastasis and unfavorable prognosis (El-Rifai et al, 2001;Tajima et al, 2007), while Hp infection has been proven to be more relevant to GAC development (Xue et al, 2011). In the subgroup analyses by type of gastric cancer, we found significantly increased risk with all genetic models in GAC subgroup; however, nearly no remarkable changes in risk estimates was observed in CAC and GSCC subgroups for the NQO1 gene C609T polymorphisms.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, it might be a special subtype or an independent entity of gastric carcinoma. Maeda et al [8] reported that the cardiac carcinoma had a higher rate of lymph node metastasis and unfavorable prognosis than did noncardiac tumors [9,10]. Meanwhile, Helicobacter pylori (Hp) infection was proven to be a key factor in adenocarcinomas of distal stomach, whereas the role of Hp in cardiac tumors was controversial [11,12].…”
mentioning
confidence: 97%
“…In the past several years, the incidence of AGC exhibited an increasing trend in the high-incidence areas of gastric adenocarcinoma in China [4,5]. Recent studies indicate that AGC and adenocarcinoma of the distal stomach (ADS) differ in their clinicopathologic and epidemiological characteristics [6,7]. However, the etiology of AGC and its relation to ADS remain unsettled.…”
Section: Introductionmentioning
confidence: 98%